PENGARUH AUDIT INTERNAL, INTELLECTUAL CAPITAL, DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2013-2016) - Sri Candra Asih; Aditya Septiani (Diponegoro Journal of Accounting, 2018)
The aim of this research is to analyze the influence of internal audit, intellectual capital, and good corporate governance to companies’ financial performance. The population of this research is banking companies which are listed in Indonesia Stock Exchange from 2013 to 2016. The sampling method of this research is purposive sampling with 43 companies as population and 19 companies selected as sample. Data used are annual reports which are downloaded from Indonesia Stock Exchange website. The results showed that partially there was a positive influence between internal auditors and Intellectual capital on financial performance. But there is no significant influence between Good Corporate Governance on financial performance. And overall there is a significant influence on the company's financial performance.